Wielowymiarowość kreatywności w edukacji = Multidimensionality of creativity in education - Rongińska, Tatiana (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper attempts to analyze the categories of creativity in relation to the tasks of modern education. Creativity is presented in the aspects of adaptation, mental health, intellect and cognitive structure development. Based on the presented content of the components of creativity, the author proposed her own definition of the concept, focusing on its major dimensions, and demonstrated the possibilities to enhance the individual?s creativity in the process of education.
Keywords: adaptacja; edukacja; kreatywność; stopnie swobody; zdrowie psychiczne; adaptation; education; creativity; degrees of freedom; mental health